2012
DOI: 10.1161/strokeaha.111.645184
|View full text |Cite
|
Sign up to set email alerts
|

Higher Stroke Unit Volume Associated With Improved Quality of Early Stroke Care and Reduced Length of Stay

Abstract: Background and Purpose— Specialized stroke unit care improves outcome among patients with stroke, but it is unclear whether there are any scale advantages in costs and clinical outcome from treating a larger number of patients. We examined whether the case volume in stroke units was associated with quality of early stroke care, mortality, and hospital bed-day use. Methods— In a nationwide population-based cohort study, we identified 63 995 patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 33 publications
3
28
1
2
Order By: Relevance
“…1 Other studies that have examined hospital stroke volume and outcome relationship have shown no benefit in mortality across volume categories; however, most of these studies had few small-volume hospitals, and those considered small had volumes <250. 7,8 Ogbu et al 8 found similar results to our study when hospital quartiles were categorized as small volume being considered <50 patients, and a previous Canadian study found that only the highest volume quartile shows significantly lower mortality rates compared with the lowest quartile. The inconsistent results across countries suggest that the effect of patient volumes on outcomes may differ in each country and dependent on volume categories selected.…”
Section: Discussionsupporting
confidence: 87%
“…1 Other studies that have examined hospital stroke volume and outcome relationship have shown no benefit in mortality across volume categories; however, most of these studies had few small-volume hospitals, and those considered small had volumes <250. 7,8 Ogbu et al 8 found similar results to our study when hospital quartiles were categorized as small volume being considered <50 patients, and a previous Canadian study found that only the highest volume quartile shows significantly lower mortality rates compared with the lowest quartile. The inconsistent results across countries suggest that the effect of patient volumes on outcomes may differ in each country and dependent on volume categories selected.…”
Section: Discussionsupporting
confidence: 87%
“…This finding agrees with findings from a nationwide Danish study 10 but not with most other studies on stroke patient volume. [3][4][5][6][7][8][9] It seems that, in some contexts, it is possible to uphold the same quality of stroke care in small as in large hospitals.…”
Section: Discussionsupporting
confidence: 91%
“…process-driven care. 21 The unanswered question is, does quality of patient/family discussions regarding feeding decisions suffer at the expense of efficiency? Strategies that incorporate family discussions into processes of care 22 and standardization of the approach with tools such as decision aids 23 may help to prevent overlooking key dialogues that patient's and their families may find important.…”
Section: Discussionmentioning
confidence: 99%